Faktor yang Berhubungan dengan Komitmen Pencegahan Penularan Tuberkulosis Paru - Giri, Dewi Dwipayanti; Sary, Lolita; Perdana, Agung Aji (Jurnal Kesehatan, 2022)
Tuberculosis (TB) is one of the top ten causes of death and is a top priority in the world. Bandar Lampung city is one of the cities with a low CDR of 63% in 2019, which indicates that TB transmission is still high. The theory of the Health Promotion Model in which prevention can be done by changing behavior is reinforced by a commitment to plan action. The purpose of the study was to determine the factors related to the commitment to prevent pulmonary TB transmission at Bandar Lampung City Health Center in 2021. This type of research was quantitative with a cross-sectional approach. The sampling technique was multistage cluster-random sampling so 66 respondents were obtained. Data analysis was univariate, bivariate, and multivariate. There is a relationship between perceived barriers (p-value=0,015), affect related-activity (p-value=0,015) and perceived interpersonal influence (p-value=0,002) with commitment in prevention. Meanwhile, perceived benefits (p-value=0,143), self-efficacy (p-value=0,666) and perceived situational influence (p-value=0,903) were not. Perception of interpersonal influence is the most dominant factor related to the commitment to prevent pulmonary TB transmission (OR:11,52 (2,38-55,57)).Â